The expected impact and future of the ILCA Subhumid Zone Programme - Kaufmann, Ralph R. von (International Livestock Centre for Africa, 1986)
Discusses potential impacts of ILCA's subhumid zone programme in Nigeria in terms of the direct benefits accruing to producers from adopting its intervention packages and indirect spinoffs from a better basis for research & development strategies in the livestock sector arising from a better understanding of complex sociological cultural, economic, ecological, agronomic & livestock management interactions constituting the livestock production system gleaned from livestock system research. Suggests 9 priority items for future research with an emphasis on component research & intervention testing.